A Bibliometric Analysis of Profit Loss Sharing (PLS) in Islamic Banking Research Using Vosviewer Application - Fahamsyah, Mohammad Hatta; 'Ainulyaqin, Muhammad Hamdan (Perisai : Islamic Banking and Finance Journal, 2023)
The aim of this investigation is to conduct a systematic examination of bibliometric data analysis utilizing VOS Viewer and to present a comprehensive, step-by-step demonstration. The analysis is intended to assist individuals who are utilizing VOSviewer for the first time in easily accessing and utilizing the software. This study uses VOSviewer's mapping tool to provide data analysis on Islamic banking profit loss sharing (PLS) and its evolution over his five years (2018-2023). The methods used were qualitatively descriptive to explain the performance of econometric literature analysis by creating network visualizations of selected topics. The search results found 996 relevant published journals from 2018 to 2023, grouped into 10 categories by year of publication. Once the journal data had been categorized, from our analysis, it was found that there were 996 articles related to profit sharing in Islamic banking that were published within the period of 2018 to 2023. Consequently, it was deduced that profit and loss sharing in Islamic banking could be linked to various other research domains, indicating that there are ample opportunities to uncover new perspectives on this subject. Additionally, this research aims to provide researchers with a source to identify promising research areas and to choose research topics.